(untitled) (Indonesian Journal of Agrarian Law, 2026)
Land title certificates serve as strong evidence of ownership for certified buyers. However, legal certainty and legal protection for such buyers can be undermined when a lawsuit filed to defend their rights is deemed obscuur libel (vague) and left unexamined on its merits. This study analyzes legal certainty and legal protection for certified buyers based on Judgment No. 138/Pdt.G/2024/PN Semarang, a land ownership dispute case. It employs a normative legal method, drawing on primary sources such as Law No. 5 of 1960, Government Regulation No. 24 of 1997, and relevant court decisions, along with secondary sources including books and journals. The findings show the Plaintiffs fulfilled the formal and material requirements of certified buyers: a valid deed of sale, a registered certificate of ownership, and sixteen years of physical possession. Nevertheless, the Panel of Judges declared the lawsuit inadmissible (niet ontvankelijke verklaard) since the legal basisan unlawful actwas conflated with the request to validate the sale and certificate. Consequently, the court’s review was confined to formal matters and did not reach the substantive issue of land ownership status. The study further compares this ruling with three other decisions sharing similar formal characteristics. It concludes that legal certainty for certified buyers remains suboptimal, as legal protection through litigation is often halted at the formal admissibility stage due to obscuur libel. The study further recommends that lawsuits be drafted clearly and systematically to prevent formal ambiguities that obstruct substantive judicial review.